Effect of Buteyko Breathing Technique on Haemodynamic Parameters and Functional Capacity in Subjects with Primary Hypertension. - Arora, Rachna; Dhokpatil, Shruti; Verma, Chhaya; Rajadhyaksha, Girish (Indian Journal of Physiotherapy & Occupational Therapy)
The Buteyko Breathing Technique (BBT) has been found to be effective in the treatment of Asthma, Obstructive Airway Disease and other diseases. Its effect on Hypertension has not been studied. Aim and Objectives: To study the effect of Buteyko Breathing technique for 4 weeks on Hemodynamic parameters and functional capacity in subjects with primary hypertension. Methodology: Parallel group study design in which 66 subjects from Hypertension OPD of Tertiary Health Care Centre were enrolled after taking their consent and Institutional Ethical approval. The subjects were randomly allocated to Control (N=33) (receiving standard treatment of care) and Experimental (N=33) (receiving Buteyko and standard treatment of care). Standard treatment of care included medication and educational videos on Hypertension, its complications and management. Buteyko Breathing Technique included supervised session of 30 minutes using a video once in a week for 4 weeks. Subjects were informed to perform these exercises at home daily. Results: The experimental group showed a significant reduction in SBP (p=0.00), DBP (p=0.00), Resting HR (p=0.00) and a significant improvement in Control Pause (p=0.00) and 6MWD (p=0.00). There was a mean reduction in SBP of 8.6 + 6.31 mmHg (95% CI, 10.84- 6.36 mmHg) and in DBP of 4.606 + 4.34 mmHg (95% CI, 6.14-3.06mmHg). Conclusion: Buteyko Breathing Technique has a positive effect on Haemodynamic parameters and functional capacity in subjects with Essential Hypertension.